2013
DOI: 10.1002/jgrg.20109
|View full text |Cite
|
Sign up to set email alerts
|

Annual budget and seasonal variation of aboveground and belowground net primary productivity in a lowland dipterocarp forest in Borneo

Abstract: [1] Tropical forests are thought to have among the highest values of net primary productivity (NPP) on Earth, but comprehensive data on NPP have rarely been collected for tropical forests, especially outside of the Neotropics. In this study, we quantify aboveground and belowground NPP, along with additional environmental factors over a 1-2 year period in a lowland dipterocarp forest in Borneo. The site is characterized by high annual rainfall and typically no month of the year when the forest is under water st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 107 publications
2
58
2
Order By: Relevance
“…In tropical forests, strong spatiotemporal variation in these losses makes quantifying and tracking them highly challenging. Illustrating this variation are the contrasting losses from two 1 ha plots in a Borneo forest in each of three intervals (LAMBIR site; Kho et al, 2013; Table 11). Tropicalforest disturbance regimes predominantly involve frequent small-scale canopy gaps (< 150 m 2 ) caused by branchfalls or treefalls; larger forest openings from storms, blowdowns, or extreme drought are increasingly rare in time and space as these disturbances increase in size (Chambers et al, 2013;Gloor et al, 2009;Magnabosco Marra et al, 2014;Marvin et al, 2014;di Vittorio et al, 2014).…”
Section: Tree Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…In tropical forests, strong spatiotemporal variation in these losses makes quantifying and tracking them highly challenging. Illustrating this variation are the contrasting losses from two 1 ha plots in a Borneo forest in each of three intervals (LAMBIR site; Kho et al, 2013; Table 11). Tropicalforest disturbance regimes predominantly involve frequent small-scale canopy gaps (< 150 m 2 ) caused by branchfalls or treefalls; larger forest openings from storms, blowdowns, or extreme drought are increasingly rare in time and space as these disturbances increase in size (Chambers et al, 2013;Gloor et al, 2009;Magnabosco Marra et al, 2014;Marvin et al, 2014;di Vittorio et al, 2014).…”
Section: Tree Mortalitymentioning
confidence: 99%
“…A study in the central Amazon combining remote sensing and ground observations (di Vittorio et al, 2014) found mortality losses to follow a power-law distribution with disturbed area, up to and including the region's extremely large blowdowns; these researchers concluded that the biomass losses observed solely in existing plots would be an inaccurate indicator (biased low) of landscape-scale dynamics. A separate compli- Kho et al (2013). cation is the disproportionate influence on biomass stocks from the deaths of scattered very large trees. In French Guianan old-growth forest (Rutishauser et al, 2010), such tree deaths were found to largely drive the heterogeneity in biomass dynamics among plots and through time.…”
Section: Tree Mortalitymentioning
confidence: 99%
“…Tropical rainforests in nearby south-east Asia often show little or no clear seasonal dynamics in canopy cover and productivity (Kho et al, 2013) but are well known for synchronous mast fruiting with a return frequency of around 2-10 years (Visser et al, 2011). The general flowering in these forests that is associated with these mast fruiting events has been shown to be triggered by irregular droughts (Sakai et al, 2006).…”
Section: Tropical Rainforestmentioning
confidence: 99%
“…Although much of the belowground allocation returns to the atmosphere relatively rapidly (80 % was lost as CO 2 within one year in a plantation in Hawaii; Giardina et al 2004), the belowground C flux can make a considerable contribution to the soil organic matter in some ecosystems (e.g., Clemmensen et al 2013). Root growth occurs mainly in the wet season in seasonal tropical forests, particularly during the transitions between seasons (Cavelier et al 1999;Kho et al 2013;Yavitt and Wright 2001), while fine root mortality occurs mainly during the dry season (Kummerow et al 1990). A study on Barro Colorado Island reported that dead fine roots disappear quickly (Yavitt and Wright 2001), so it is possible that death and decomposition of very fine roots and associated mycorrhizal fungi might contribute to the dry season decline in soil organic matter.…”
Section: Seasonal Dynamics Of Soil Organic Mattermentioning
confidence: 99%